Electrical resistivity tomography for aquifer imaging - Pant, Dipak Raj (Journal of Nepal Geological Society, 2000)
Aspects related to the development of a technique called electrical resistance tomography for producing two- or three dimensional subsurface images of an aquifer have been discussed. The technique is based on the automated measurement and computerised analysis of electrical resistivity changes caused by natural or man-made processes. A subsurface region of the aquifer to be studied is sampled by transmitting electrical energy through it along many paths of known orientations, and the apparent resistivity data derived are used to construct a cross-section al image of the region of interest. The physical model experiments and field experiments show that the presented method is effective and flexible for crosshole resistivity imaging of aquifer with bipole-bipole electrode configurations.